Responses of Pea (Pisum sativum) Growth and Yield to Residual Effects of Organic and Urea Fertilizers from Previous Crop - S. Fallah; N. Ghasemi Siani; A. Salehi (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2016)
Application of organic manure in organic farming and long-term mineralization may lead to residual effects on the succeeding crop. So, residual effects of combined cattle manure and urea fertilizer of previous crop (black cumin) on growth and yield of pea were examined in a randomized complete block design. Treatments included of  cattle manure (CM), urea (U), three ratios of CM+U full dose application (2:1; 1:1; 1:2) and three ratios of CM+U split application (2:1; 1:1; 1:2), and unfertilized control to previous crop (black cumin) in 2012. Pea planted without any fertilizer in 2013. There was no significant difference between control and residual of urea treatment for some parameters including dry matter in flowering stage, plant nitrogen and phosphorus concentration, plant height, yield components, grain yield and biological yield of pea. Biological and grain yields were greater under both residual of cattle manure treatment and integrated treatments compared to residual of urea treatment. The highest grain yield (4000 kg ha-1) was observed in residual of CM:U full dosed application treatment, to the extent that grain yield in this treatment indicated a 1.5-fold increase in comparison with residual of urea treatment. The highest biological yield (8325 kg ha-1) was obtained in residual of CM treatment, though it was not significant different from that of residual of CM:U (1:2) treatments. In general, although residual of urea fertilizer did not leave a notable effect on pea production, but production of this crop relying on residual of cattle manure deems effective to lowering of fertilization cost and ameliorating environmental contaminations.